Water security index for four neighbour cities in the Aegean region incorporating future challenges - Marangoz, Deniz. (Thesis (M.S.)-Bogazici University. Institute of Environmental Sciences, 2019., 2019)
Water security has been a global issue since accessing clean water is a challenge for poorer communities. This problem is becoming even more complex as water resources continue to deplete. Climate change and population growth should now also be taken into consideration in water planning, since unstable weather conditions and increasing demands of the population would make it harder to predict future water supply levels. In this study, a water security index for the 4 neighbour provinces in the Aegean region (Aydın, Denizli, Muğla and Uşak) is developed through the adoption of Pressure-State-Response (PSR) method, which is based on the cause-effect relations between human activities and the environment. Baseline index calculations show that the study area’s water resources are currently in “poor conditions”, whereas the current water security of the region is in “medium conditions”. Integration of climate change scenarios (RCP8.5 and RCP4.5) and population growth projections into baseline results do not alter the baseline conditions, yet when combined, they substantially pull the water security level of the area of interest down. Sole effect of RCP8.5 scenario on the water resources of the 4 cities as a whole is also significant.
Keywords: Water security -- Turkey -- Aegean region.